Sero-Prevalence of Brucellosis in Pigs of Bhaktapur, Kavre and Banke Districts of Nepal - Sharma, Shilu; Khanal, Doj Raj; Panth, Yuvraj (International Journal of Applied Sciences and Biotechnology, 2017)
Brucellosis; a zoonotic disease which is caused by Brucella sp. viz; abortus, melitensis, ovis, canis, suis, in Nepal is regarded as one of the occupational and public health hazards for veterinarians, animal attendants, dairy man, slaughter-house workers, butchers and meat sellers. This study aimed to determine the prevalence of brucellosis in pigs of Bhaktapur, Kavre and Banke districts of Nepal. Serum samples of 231 pigs were collected purposively of which, 78 samples were from Bhaktapur, 85 from Kavre and 68 from Banke districts. Blood samples were collected from the jugular vein of the pigs and were centrifuged to separate the serum from the blood. The separated serum samples were stored at -20°C in the NARC lab till the test was done. Out of 231 samples, 3.90% (9/231) of samples were found to have sero-positivity towards brucellosis by using indirect ELISA test through ID Vet iELISA kit 2016. Fisher exact test was used to find association between variables. There was no significant differences (p>0.05) on sex-wise prevalence. This study shows a potential threat to the public health sector of the country along with the degradable impacts on animal health including the economy of farmers. Thus, timely implementation of appropriate preventive and control strategies should be adopted to eradicate the disease.Int. J. Appl. Sci. Biotechnol. Vol 5(4): 466-469